Penerapan Metode Pembelajaran Blended Learning Terhadap Kemampuan Renang Gaya Dada Mahasiswa STKIP YPUP Makassar - AKBAR YUSUF; ANDI SAHRUL JAHRIR (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aims to obtain answers to problems that occurred during the COVID-19 pandemic, the effect of blended learning on the breaststroke swimming ability of STKIP YPUP Makassar students. This research is descriptive of the independent variable and the dependent variable. The population and sample were students of STKIP YPUP Makassar selected by random sampling, obtained as many as 30 people who were selected at random or random sampling. The data analysis technique used was t-test analysis using computer facilities through the SPSS program.Based on the results of data analysis, it can be concluded as follows: There is an effect of blended learning on the breaststroke swimming ability of STKIP YPUP Makassar students with an average increase value of 2.414 with a significance value of 0.000 <0.05